Peyton Anderson: capstone - Anderson, Peyton, artist (Colorado State University. Libraries, 2023)
The artist's statement: Many of us are asked what we want to do when we grow up. I thought about how I want to help people be happy. If I make someone's day a little better through what I do, I am successful. My clients happiness is especially important, for it will further reflect to their audience. Design allows me to anchor in these core values. I strive to create works that balance a fun subject with sophisticated, clean designs, or a serious subject with animated, organized imagery. Colors are one of my most reliable assets for hooking the audience and upholding the mood of the piece. I often add a clever element to my works, whether it be subject, font, or a tagline to be a feature that lighten the composition. A picture is worth a thousand words, while a thousand words can paint a picture, so I often begin taking note of an idea in sketch or letter form. From there the idea is brought to a digital arena; Adobe Creative Suite. I intermingle several programs to achieve optimal results. After review, I translate the feedback into the original design to best suit the vision of the client. Through pleasing them, I establish more confidence in my practice.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design